Kajian Hermeneutik Kritik Sosio-Retoris Markus 10:35-45 dan Implikasinya Bagi Mahasiswa Fakultas Teologi UKIT - Laloan, Rivaldo Joshua; Sendow, Mieke Nova (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
The Bible is clearly mentioned in biblical book that “For even the Son of Man did not come to be served, but to serve, and to give His life a ransom for many”. Mark 10:45 NKJV. Through hermeneutics Socio-Rhetorical criticism, it is becoming the reflection to every believers that this is the good example depicted by Jesus of how a servant shows their identity. The call of being a servant is to always be prepared to serve sincerely and wholeheartedly and willing to sacrifice even if it is necessary to be anguished. What is the essence of being a “Doulos” (slave) if the orientations assessment is only to be served and not to serve. In spite of being a slave is having a great responsibility in it, but every believers needs to be prepared to every process and strive to the very end.